Implementation of Innovative Learning with the Project Based Learning (PjBL) Model in Anti-Corruption Education Courses - Dyan Yuliana (PT FORMOSA CENDEKIA GLOBAL, 2022)
So far, the learning process has only focused on improving learning outcomes but has not provided guidance on students' creative talents in being creative during lectures, so that students cannot develop their creativity to the fullest. This study aims to determine the results of implementing innovative learning with the Project Based Learning (PjBL) model in growing and increasing student creativity in Anti-Corruption Education courses. The research method used is descriptive method with a qualitative approach in which the data is obtained from observations and interviews with a descriptive analytical or critical analytical style, namely examining the primary ideas regarding the scope of the problem that are believed by relevant secondary ideas. The results of this study concluded that the implementation of innovative learning with the PjBL model can grow and increase student creativity, so that it is effectively used in the learning process of Anti-Corruption Education courses. In addition, students can take an active role in preventing corrupt behavior on campus and society.